(untitled) (Journal of Management and Social Sciences, 2019)
The objectives of this article are in twofold. First, the article undertakes a critical conceptual and theoretical analysis of the state with focus on concept and the emergence of the state. Second, it assesses the performance of the Nigerian state vis-Ã -vis security issues in the Fourth Republic. Adopting the historical qualitative research design and through a critical examination of extant secondary data and the adoption of the social contact theory and the political economy approach as the theoretical framework of analysis it finds that the inability of the Nigerian state to provide adequate security for the lives and properties of its citizens is the major driving force of ethnoreligious cum socio-political conflicts. This has put the nation in the comity of fragile states. The study, however, concludes by suggesting that there is an urgent need on the part of the government to put in place adequate and effective security measures to stem violent conflicts in the polity.